Expenditure and Ecotourism: Predictors of Expenditure for Whale Shark Tour Participants - Jones, Tod; Wood, David; Catlin, James; Norman, B. (Channel View Publications, 2009)
Whale shark tourism is an icon industry in Western Australia and a prominent example of successful ecotourism. In 2006, Whale shark tour participants spent $6.0 million in the Ningaloo Coast region of Western Australia and added between $2.4 million and $4.6 million to the regional economy in direct expenditure. However, to date no research has been conducted on the predictors of whale shark tour participants expenditure. In this paper, we assess the importance of visitor expenditure for ecotourism, assess the predictors of the expenditure of whale shark tour participants and discuss how this information can contribute towards ecotourism goals. The data analysed here was collected through a survey distributed to participants between April and June, 2006. We assess a range of variables for their relationship to individual expenditure per trip and determine that duration of stay, household income, age, staying in a hotel, trip motivation, and being from North America or Southeast Asia positively correlate with individual expenditure per trip. Group size, and coming from Germany or the UK and Ireland negatively correlate with expenditure. In addition to identifying future steps, we also discuss the relevance of our finding that more motivated participants have a higher expenditure for ecotourism.